IDH1/2 Mutations in Patients With Diffuse Gliomas: A Single Centre Retrospective Massively Parallel Sequencing Analysis - Sporikova, Zuzana; Slavkovsky, Rastislav; Tuckova, Lucie; Kalita, Ondrej; Megova Houdova, Magdalena; Ehrmann, Jiri; Hajduch, Marian; Hrabalek, Lumir; Vaverka, Miroslav (Applied immunohistochemistry & molecular morphology, 2022)
Patients below 55 years were genetically studied because the prevalence of isocitrate dehydrogenase 1 (IDH1) decreases in older patients and on grounds of cost-effectiveness, as suggested by the World Health Organization (WHO) in 2016. The aim of our study was to use novel massively parallel sequencing (MPS) approaches to examine rare variants of IDH1/2 in Czech diffuse astrocytic and oligodendroglial tumors (gliomas) patients below 55 years of age who had been immunohistochemically (IHC) diagnosed as IDH1 R132H negative. The IHC IDH1 status (wild type or mutant) of 275 tissue samples was analyzed using antibodies against the IDH1 R132H protein. Sixty-three samples of 55 years old patients with IHC IDH1 WT status were genotyped using two different MPS technologies to detect rare IDH1 and IDH2 variants. The tiered IHC (60 positive) and molecular (10 positive) approach thus revealed that 70 of the 275 samples (25%) bore IDH1/IDH2 mutations. The combined molecular and IHC approach thus revealed that 70 of the 275 samples (25%) considered in the study bore IDH1/IDH2 mutations. IHC detection of the IDH1 R132H variant should be routinely complemented with MPS to detect rare IDH1/2 variants in glioma patients below 55 years of age with negative IHC result of IDH R132H variant.
Keywords: nádory mozku; senioři; vysoce účinné nukleotidové sekvenování; Brain Neoplasms; Isocitrate Dehydrogenase; Middle Aged; mutace; isocitrátdehydrogenasa; Mutation; retrospektivní studie; Glioma; Humans; Aged; High-Throughput Nucleotide Sequencing; Retrospective Studies; gliom; lidé; lidé středního věku